Handbook of health psychology - Baum, Andrew
Gồm: Overarching Frameworks and Paradigms; Cross-Cutting Issues; Risk and Protective Factors; Macro-Level and Structural Inï¬‚ uences on Health; pplications of Health Psychology; References: 210 - 217